2011
DOI: 10.1002/pen.22150
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐induced crystallization of isotactic polypropylene studied by simultaneous light intensity and rheological measurements

Abstract: We investigate the effects of high shear rate and a melt‐insensitive, organophosphate nucleating agent on shear‐induced crystallization of four isotactic polypropylenes using a sliding plate rheometer under isothermal, low‐supercooling conditions. We used a bifurcated optical fiber probe to measure light intensity and a shear stress transducer to monitor the simultaneous viscoelastic response to small‐amplitude oscillatory shear. The two techniques complement each other; at early times of crystallization, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…We have shown previously that the appearance of birefringent light-scattering material precedes crystallinity as measured by the Raman spectroscopy. 17 Prior results have also shown that light scattering appears well before crystallinity as measured by dilatometry, 41 rheology, 42 and x-ray scattering. 43 The explanation for the appearance of light scattering prior to other crystallinity measurements is not resolved, but certainly the relative sensitivity of each technique to crystallization must be taken into account.…”
Section: B Hdpe Crystallizationmentioning
confidence: 89%
“…We have shown previously that the appearance of birefringent light-scattering material precedes crystallinity as measured by the Raman spectroscopy. 17 Prior results have also shown that light scattering appears well before crystallinity as measured by dilatometry, 41 rheology, 42 and x-ray scattering. 43 The explanation for the appearance of light scattering prior to other crystallinity measurements is not resolved, but certainly the relative sensitivity of each technique to crystallization must be taken into account.…”
Section: B Hdpe Crystallizationmentioning
confidence: 89%
“…When “thread‐like” nuclei become denser, cylindrulites impinge prior to significant noncrystallographic branching and a highly oriented morphology forms. Currently, studies of flow conditions on the onset of oriented structures are mainly based on using laboratory plate‐plate rheometer, sliding plate rheometer or customized pressure driven flow cell; very few attempts have been made to study or validate such thresholds under non‐isothermal industrial processing conditions …”
Section: Introductionmentioning
confidence: 99%
“…In general, flow enhances the kinetics of crystallization immensely compared to that of quiescent crystallization by stretching and orienting molecules in the direction of flow. Flow parameters such as strain and strain rate have been found to play a critical role in this phenomenon …”
Section: Introductionmentioning
confidence: 99%
“…Flow parameters such as strain and strain rate have been found to play a critical role in this phenomenon. 1,[7][8][9][10][11][12][13][14][15][16][17] The effect of flow on the kinetics of crystallization was studied previously. [18][19][20][21][22][23][24][25][26][27] In particular, Coccorullo et al 23 used optical microscopy to determine nucleation and growth rate of iPP under weak shear deformation (_ c 5 020.3 s 21 ) using the Linkam shearing cell (CSS 450).…”
mentioning
confidence: 99%